The impact of small-for-gestational-age Status on the outcomes in very-Low-birth-weight (VLBW) premature infants: a prospective cohort study in Taiwan - Lin, Chia-Ying; Chang, Hung-Yang; Chang, Jui-Hsing; Hsu, Chyong-Hsin; Jim, Wai-Tim; Peng, Chun-Chih; Chen, Chia-Huei (Frontiers in Pediatrics, 2023)
The impact of small-for-gestational-age (SGA) on very-low-birth-weight (VLBW) premature infants remains inconclusive. This study aimed to assess the effects of being born SGA status on the short-term and long-term outcomes in VLBW preterm infants.We conducted a population-based, prospective cohort study on VLBW preterm infants born in Taiwan between 2012 and 2017. Sociodemographic, neonatal, growth and neurological data at 2 years of corrected age were collected. A total of 4243 VLBW infants born at 24 through 32 completed weeks' gestation participated in this study, of whom 1005 had SGA status defined as a birth weight < 10th percentile of gestation, and 3238 did not (the non-SGA group).We compared the risks of short-term outcomes (neonatal mortality and morbidities), long-term outcomes (growth status, including weight, height, and head circumference < 10th percentile, and neurodevelopmental impairments at 2 years of age). Subgroup analysis was performed by stratification of gestation age (GA): GA 24-26, 27-29 and 30-32 weeks.In the analysis of short-term outcomes, the SGA group had an increased risk of neonatal mortality (adjusted odds ratio [OR]=2.66, 2.99, and 2.19, respectively) in all GA subgroups in comparison with the non-SGA group (p<0.05). The SGA group had a significantly increased risk of bronchopulmonary dysplasia in GA 27-2 29 and 30-32 weeks (adjusted OR=2.11 and 1.86, respectively). We also found that there was an increased risk of severe retinopathy of prematurity in GA 24-26 and 27-29 weeks in the SGA group compared with the non-SGA group (adjusted OR=1.68 and 1.59, respectively).In the analysis of long-term outcomes, the SGA group had a significantly increased risk of NDI throughout all GA subgroups (adjusted =1.94, 1.33, and 1.35, respectively) in comparison with the non-SGA group. The SGA groups also had an increased risk of growth status < 10th percentile at 2 years of age (p<0.05).Conclusions: SGA VLBW premature infants had higher risks of neonatal death, growth status < 10th percentile, and NDI at 2 years of corrected age compared with the non-SGA premature infants. Prenatal surveillance, postnatal attention, and long-term follow-up are warranted to improve the outcomes of VLBW SGA premature infants.